2021
DOI: 10.3390/rs13224544
|View full text |Cite
|
Sign up to set email alerts
|

A Google Earth Engine Application to Retrieve Long-Term Surface Temperature for Small Lakes. Case: San Pedro Lagoons, Chile

Abstract: Lake surface water temperature (LSWT) is a crucial water quality parameter that modulates many lake and reservoir processes. Therefore, it is necessary to monitor it from a long-term perspective. Over the last decades, many methods to retrieve LSWT fields from satellite imagery have been developed. This work aims to test, implement and automate six methods. These are performed in the Google Earth Engine (GEE) platform, using 30 m spatial resolution images from Landsat 7 and 8 satellites for 2000–2020. Automate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Our results clearly show a spatial pattern varying from higher Chl-a values in the northern zone compared to the southern zone. These results are in agreement with the research of Pedrero-Guarda et al, [23], which identified spatial variations in temperature in Laguna Grande, possibly attributed to a heat island effect. This effect causes temperature differences, with higher temperatures near urban areas (northern part) and lower temperatures in vegetated regions.…”
Section: IIIsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results clearly show a spatial pattern varying from higher Chl-a values in the northern zone compared to the southern zone. These results are in agreement with the research of Pedrero-Guarda et al, [23], which identified spatial variations in temperature in Laguna Grande, possibly attributed to a heat island effect. This effect causes temperature differences, with higher temperatures near urban areas (northern part) and lower temperatures in vegetated regions.…”
Section: IIIsupporting
confidence: 93%
“…Since 2014, sampling is performed only at the Sector Centro 2 station, but the available information only includes three sampling missions by year between 2014 and 2016. Assuming four measurements per year, the percentage of missing data at stations Centro, Desagüe, Sur and Centro 2 between 1988 and 2016 is 28% [23]. These factors serve as a focal point to address the main problem that this study aims to solve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) Assessment of the spatial-temporal variability Finally, results clearly showed a spatial pattern with higher Chl-a values in the northern zone compared to the southern zone. These results are in agreement with those of Pedrero-Guarda et al [25], who identified spatial dynamics of temperature in Laguna Grande, possibly attributed to a heat island effect. This effect causes temperature differences, with higher temperatures near urban areas (northern part) and lower temperatures in vegetated regions.…”
Section: (Ii) Development Of An Empirical Retrieval Modelsupporting
confidence: 93%
“…This was achieved through a multitemporal analysis using satellite imagery. Recently, Pedreros-Guarda et al [25], implemented six automated methods for retrieving the surface water temperature of the lagoon using satellite thermal imagery.…”
Section: Introductionmentioning
confidence: 99%